Strategi Pembelajaran ADA TAWA CERIA dalam Menulis Teks Narasi Cerita Imajinatif - Hariadi, Sutriono (University of Brawijaya, 2018)
Language learning based on the curriculum of 2013 is text-based learning. Various types of text that can be learned by students. One type of text to be studied is the text narration of the story of the imagination. In this learning process must surely require a specific strategy so that the learning objectives are achieved. The strategy is ADA TAWA CERIA is one strategy that can be chosen by the teacher. This strategy is the creation of cooperative learning model. This strategy is the implications of scientific learning. In the strategy there is a ADA TAWA CERIA, offered a new form in the teach students to write a narrative story of imagination.